2019
DOI: 10.4102/curationis.v42i1.1943
|View full text |Cite
|
Sign up to set email alerts
|

Use of scenarios to explore conflict management practices of nurse unit managers in public hospitals

Abstract: Background Workplace conflict is common among nurses globally. Learning how to manage it may reduce related adverse consequences. Inappropriate management of conflict is attributed to decreased productivity, poor morale and financial loss for organisations. Nurse unit managers can play a key role by effectively managing workplace conflict in the units. Objectives To explore how nurse unit managers manage conflict in public hospitals and subsequently to make recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
2
15
1
Order By: Relevance
“…Ganz et al (2014) reported a similar finding in Israel. However, the result is inconsistent with the work of Moeta and Du Rand (2019) in which unit-level FLNMs in South Africa appeared to have challenges in dealing with conflict between individuals or generally in the unit and intervened inappropriately.…”
Section: Leadership Competencies Of First-line Nurse Managerscontrasting
confidence: 58%
See 1 more Smart Citation
“…Ganz et al (2014) reported a similar finding in Israel. However, the result is inconsistent with the work of Moeta and Du Rand (2019) in which unit-level FLNMs in South Africa appeared to have challenges in dealing with conflict between individuals or generally in the unit and intervened inappropriately.…”
Section: Leadership Competencies Of First-line Nurse Managerscontrasting
confidence: 58%
“…As nursing units are human societies, conflicts are inevitable. However, poor management of conflict has been linked to low morale, decreased productivity, job dissatisfaction, financial loss for organizations and poor workflow (Moeta and Du Rand, 2019). Therefore, resolving conflicts that arise at the unit level is an essential endeavor critical to all FLNMs.…”
Section: Leadership Competencies Of First-line Nurse Managersmentioning
confidence: 99%
“…This is crucial because the importance of effective conflict management among nurse managers has been strongly highlighted, which influences staff nurses' intention to stay. [ 7 18 21 ] In general, this study highlights the need to enhance nurses' skills for conflict management. The literature shows that along with nurses, other healthcare providers also need such training.…”
Section: Discussionmentioning
confidence: 93%
“…Resolving conflicts and challenges are pertinent issues faced by nurse managers at the unit level because of the number of different professional groups engaged in patient‐centred care. Thus, as contended by Moeta and Du Rand (2019), managers engage in a continuing scuffle to maintain discipline and control over workers. At the unit level, the nurse manager becomes the fulcrum around which the unit revolves.…”
Section: Discussionmentioning
confidence: 99%